Information and Communication Technology: A Gate or Gateway to Advance Financial Literacy - Shuttleworth, Christina Cornelia; Moolman, Jaco; Basson, Antoinette; Risenga, Arthur (International Journal of Economics and Financial Issues, 2026)
Fintech offers unique opportunities to advance financial literacy education, however its broader application is dependent on a range of socio-economic factors. This study aimed to investigate. This study aimed to uncover to what extent certain socio-economic conditions are prevalent in a developing country, such as South Africa, which are necessary for fintech-based financial literacy education interventions. To this end, a quantitative research design was used with a positivist approach with a total of 1,141 respondents. The findings indicate that South Africa possesses a solid foundation for advancing digital financial literacy, supported by widespread internet access, high levels of digital competence, and a reasonable prevalence of financial literacy skills. While current usage of digital financial education tools and apps remains limited, those who do engage with them recognize their value and potential impact. However, efforts are still needed to boost public interest and confidence in these platforms. This study could attract the interest of policymakers, researchers, advocacy groups, financial institutions and fintech companies that are intent on developing more user-friendly and accessible digital financial literacy educational content.